MiR‐182‐5p enhances in vitro neutrophil infiltration in Kawasaki disease - Li, Sung‐Chou (Mol Genet Genomic Med, 2019)
BACKGROUND: Kawasaki disease (KD) patients could develop coronary artery lesion (CAL) which threatens children's life. A previous study identified KD biomarker miRNAs that could discriminate KD patients from febrile non‐KD patients. We wonder whether these KD prediction biomarkers could be further applied to predict CAL formation in KD patients. METHODS: To examine this hypothesis, we conducted a meta‐analysis, miRNA mimic transfection, in vitro cell model and microarray assays. RESULTS: We first showed that miR‐182‐5p and miR‐183‐5p kept higher levels in the KD patients with CAL than those without CAL (p < .05). Further machine learning alignment confirmed that CAL formation could be predicted, with an auROC value of 0.86. We further treated neutrophil cells with miR‐182‐5p mimic, followed by in vitro transendotherial migration assay. As a result, miR‐182‐5p overexpression significantly (p < .05) enhanced neutrophil cells to infiltrate the endothelial layer composed of human coronary artery endothelium cells. Further microarray assay and pathway enrichment analysis showed that the genes activated with miR‐182‐5p overexpression were significantly enriched in the leukocyte transendothelial migration pathway (kegg_pathway_194, p < .05). CONCLUSION: Therefore, our study suggested that miR‐182‐5p enhanced in vitro leukocyte infiltration by activating the leukocyte transendothelial migration pathway in CAL formation in KD.